Natural history of COPD: Focusing on change in FEV1. Issue 1 (15th July 2015) - Vestbo, Jørgen; Lange, Peter
Abstract: The natural history of chronic obstructive pulmonary disease (COPD) is usually described with a focus on change in forced expiratory volume in 1 s (FEV1 ) over time as this allows for exploration of risk factors for an accelerated decline—and thus of developing COPD. From epidemiological studies we have recognized important risk factors such as smoking, exposure to biomass and occupational exposures, but we have also learnt about features such as chronic bronchitis, airway hyper‐responsiveness and asthma that seem to accelerate decline in FEV1 independent of exposures. In addition we are gradually beginning to better link early life events to subsequent risk of disease in adulthood. Although more complicated, our current understanding of COPD has come a long way from being a simple image of smoking leading to poor lungs.